2020
DOI: 10.3390/plants10010028
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network for Automatic Identification of Plant Diseases with Limited Data

Abstract: Automated identification of plant diseases is very important for crop protection. Most automated approaches aim to build classification models based on leaf or fruit images. These approaches usually require the collection and annotation of many images, which is difficult and costly process especially in the case of new or rare diseases. Therefore, in this study, we developed and evaluated several methods for identifying plant diseases with little data. Convolutional Neural Networks (CNNs) are used due to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 36 publications
(55 reference statements)
0
32
0
Order By: Relevance
“…Using an artificial neural network and a support vector machine, the pattern is identified for each species of plant. SVM has a 96.67 percent accuracy rating, whereas ANN has a 92 percent accuracy rating [8]. Ray et al ( 2017) devised a method for detecting fungal illness at an early stage, and correctly diagnosing the disease aids in its prevention.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an artificial neural network and a support vector machine, the pattern is identified for each species of plant. SVM has a 96.67 percent accuracy rating, whereas ANN has a 92 percent accuracy rating [8]. Ray et al ( 2017) devised a method for detecting fungal illness at an early stage, and correctly diagnosing the disease aids in its prevention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Image-In the convolution neural network method, net classification is highly effective. For domain-specific training, transfer learning is also employed [8,9]. When taught and evaluated for a variety of species, the results suggest that it is more accurate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The restrictions of the traditional approach have motivated researchers to develop technological proposals for the early identification of crop diseases in an accurate, fast, and reliable manner, and in order to meet the increasing demands of consumers and alleviate the environmental impact of chemical inputs on the environment and health. In this regard, several methods [6][7][8][9] have been proposed to automate the process of disease detection. These methods for automatic recognition of crop diseases are divided into two groups, direct and indirect methods [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that deep learning approaches outperform machine learning algorithms, such as support vector machine, random forest, stochastic gradient descent [ 38 ]. The development of the deep learning methods towards better disease recognition in plants included transfer learning approaches [ 39 ], implementing networks of various architectures [ 37 , 40 , 41 , 42 , 43 , 44 ], working with the limited amount of data [ 45 ], and Bayesian deep learning [ 46 ].…”
Section: Introductionmentioning
confidence: 99%